Ozaveščenost o javnem govornem nastopanju - priložnost za profesionalni razvoj učitelja - Petek, Tomaž (Jezik in slovstvo, 2012)
The teacher's ability to communicate effectively is one of the key competencies, and within its framework the role of the teacher as a public speaker plays an important part. The promotion and development of public speaking skills in pre-service teachers is important for the successful implementation of the objectives of the modern educational process, i.e., teaching in the classroom, and thus represents an opportunity for teachers to develop professionally. Due to changed views on effective teaching, and as a result of modified patterns of communication in modern society, lecturing/explanation, as a characteristic rhetoric type and one of the fundamental monologue spoken text types formed by the teacher in the classroom, has changed significantly. The teacher should therefore be well prepared in terms of content, as well as didactically and "rhetorically", before undertaking public speaking. Given that this is a complex and important skill, it is of utmost importance that students (future teachers) be properly trained for this activity while studying at the 1st level (as well as the second). In developing teachers' public speaking competencies, the focus should, among other things, be on the ability to produce relevant, comprehensible, accurate and efficient public monologue spoken texts.
Keywords: javno nastopanje; izobraževanje učiteljev; predavanje; raziskave; vprašalniki